A parallel coupled oceanic-atmospheric general circulation model - Wehner, M. F.; Bourgeois, A. J.; Eltgroth, P. G.; Duffy, P. B.; Dannevik, W. P. (Lawrence Livermore National Laboratory, 1994)
The Climate Systems Modeling group at LLNL has developed a portable coupled oceanic-atmospheric general circulation model suitable for use on a variety of massively parallel (MPP) computers of the multiple instruction, multiple data (MIMD) class. The model is composed of parallel versions of the UCLA atmospheric general circulation model, the GFDL modular ocean model (MOM) and a dynamic sea ice model based on the Hiber formulation extracted from the OPYC ocean model. The strategy to achieve parallelism is twofold. One level of parallelism is accomplished by applying two dimensional domain decomposition techniques to each of the three constituent submodels. A second level of parallelism is attained by a concurrent execution of AGCM and OGCM/sea ice components on separate sets of processors. For this functional decomposition scheme, a flux coupling module has been written to calculate the heat, moisture and momentum fluxes independent of either the AGCM or the OGCM modules. The flux coupler`s other roles are to facilitate the transfer of data between subsystem components and processors via message passing techniques and to interpolate and aggregate between the possibly incommensurate meshes.